Odpowiedzi

2009-09-19T11:55:34+02:00
3x-2y=1
x+2y=3 dodaje
4x=4
x=1 , y=1
B) x+y=5
2x+y=3 odejmuje
x=-2 , y=7
2009-09-19T11:57:13+02:00
A)
3x-2y=1
x+2y=3

3x-2y=1
x=3-2y

3*(3-2y)-2y=1
9-6y-2y=1
9-8y=1
-8y=-8
8y=8
y=1
x=3-2*1
x=1

y=1
x=1

B)
x+y=5
2x+y=3

y=5-x
2x+y=3

2x+5-x=3
x=(-2)

y=5-(-2)
y=7

x=(-2)
y=7
  • Użytkownik Zadane
2009-09-19T12:00:09+02:00
A) 3x-2y=1
x+2y=3/-2y
3x-2y=1
x=3-2y
3*(3-2y)-2y=1
9-6y-2y=1
9-8y=1/-9
-8y=-8
y=1
3x-2=1
x=1

y=1
x=1

B) x+y=5
2x+y=3
x+y=5
y=3-2x
x+3-2x=5
-x+3=5
-x=2
x=-2
-2+y=5

y=7
x=-2